2019
DOI: 10.1111/bju.14958
|View full text |Cite
|
Sign up to set email alerts
|

External validation of novel magnetic resonance imaging‐based models for prostate cancer prediction

Abstract: Objectives To validate, in an external cohort, three novel risk models, including the recently updated European Randomized Study of Screening for Prostate Cancer (ERSPC) risk calculator, that combine multiparametric magnetic resonance imaging (mpMRI) and clinical variables to predict clinically significant prostate cancer (PCa). Patients and Methods We retrospectively analysed 307 men who underwent mpMRI prior to transperineal ultrasound fusion biopsy between October 2015 and July 2018 at two German centres. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…The validation studies of Radtke et al, Pullen et al, and Saba et al were all performed in a population undergoing transperineal prostate biopsy, whereas Mortezavi et al performed their study in a cohort undergoing TRUS biopsy. [22][23][24][25] Utilizing the MRI-ERSPC-RC, all of these studies found results consistent with our study with an AUC between 0.82 and 0.87 suggesting that, although the MRI-ERSPC-RC was developed in a TRUS biopsy cohort, its usage could be implemented in patients being considered for transperineal biopsy.…”
Section: Ta B L E 1 Patient and Tumor Characteristicssupporting
confidence: 89%
“…The validation studies of Radtke et al, Pullen et al, and Saba et al were all performed in a population undergoing transperineal prostate biopsy, whereas Mortezavi et al performed their study in a cohort undergoing TRUS biopsy. [22][23][24][25] Utilizing the MRI-ERSPC-RC, all of these studies found results consistent with our study with an AUC between 0.82 and 0.87 suggesting that, although the MRI-ERSPC-RC was developed in a TRUS biopsy cohort, its usage could be implemented in patients being considered for transperineal biopsy.…”
Section: Ta B L E 1 Patient and Tumor Characteristicssupporting
confidence: 89%
“…Patients underwent and observed risks), and clinical utility (20,21). A widely adopted method to measure clinical utility is decision curve analysis (16)(17)(18)(19)(21)(22)(23)(24)(25), in which clinical net benefit is plotted against a range of relevant risk thresholds. The net benefit quantifies net true positives or true negatives corrected for the harm of false positives or false negatives (ie, unnecessary biopsy and missed csPCa), whereas the risk threshold indicates the maximum acceptable risk of missing csPCa (21,25).…”
Section: Prostate Biopsiesmentioning
confidence: 99%
“…If, by contrast, a patient or physician is more worried about potential harms of biopsy (complications and overdiagnosis), then a higher risk threshold (eg, 15%) may be adopted (25). External validation studies of published risk models demonstrated poor calibration of some models and limited net benefit at risk-averse thresholds (22)(23)(24). At a risk threshold greater than or equal to 5%, net benefit was noted for only one risk model in a German cohort (22) and none in a Swiss cohort (23) and Swedish (24) cohort.…”
Section: Prostate Biopsiesmentioning
confidence: 99%
“…(MRI-ERSPC-3/4, ModRAD, and ModDis) were 0.82, 0.85, and 0.83 [28]. Moreover, it was reported that the ERSPC-RCs could reduce unnecessary biopsy by 36%, while missing highgrade PCa in 4% of men [12].…”
Section: Discussionmentioning
confidence: 99%